Mucormycosis at the Time of COVID-19 Pandemic: A Review (Bangladesh Journal of Infectious Diseases, 2022)
Mucormycosis, an opportunistic fungal illness, has become a global health problem in the aftermath of the COVID-19 pandemic. This is mostly owing to a dramatic spike in COVID-19 infection in recent months in India, which was exacerbated by this fungal co-infection. Mucormycosis has an exceptionally high probability of death and lasting damage to the affected area. Although early action can save lives and mitigate the fungus's impact, it is frequently hard for the already overwhelmed health system in India due to the pandemic. Other variables, such as diabetes, have had a significant impact on the disease's outcome.Bangladesh Journal of Infectious Diseases, April 2022;9(Suppl_1): S55-S57